At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
### Given Data:
- Parametric equations for the particle:
[tex]\[ x = 4 \alpha \cos^3(\mu), \quad y = 4 \alpha \sin^3(\mu), \quad z = 3 \phi \cos(2 \mu) \][/tex]
### Part (a): Finding the Velocity and Acceleration
1. Velocity Components
- The velocity vector [tex]\(\mathbf{v}\)[/tex] is obtained by differentiating the position vector with respect to time [tex]\(t\)[/tex]:
[tex]\[ v_x = \frac{dx}{dt} = \frac{d}{dt}[4 \alpha \cos^3(\mu)] \][/tex]
[tex]\[ v_x = 4 \alpha \cdot 3 \cos^2(\mu) \cdot (-\sin(\mu)) \cdot \frac{d\mu}{dt} \][/tex]
[tex]\[ v_x = -12 \alpha \cos^2(\mu) \sin(\mu) \cdot \frac{d\mu}{dt} \][/tex]
[tex]\[ v_y = \frac{dy}{dt} = \frac{d}{dt}[4 \alpha \sin^3(\mu)] \][/tex]
[tex]\[ v_y = 4 \alpha \cdot 3 \sin^2(\mu) \cdot \cos(\mu) \cdot \frac{d\mu}{dt} \][/tex]
[tex]\[ v_y = 12 \alpha \sin^2(\mu) \cos(\mu) \cdot \frac{d\mu}{dt} \][/tex]
[tex]\[ v_z = \frac{dz}{dt} = \frac{d}{dt}[3 \phi \cos(2 \mu)] \][/tex]
[tex]\[ v_z = 3 \phi \cdot (-2 \sin(2 \mu)) \cdot \frac{d\mu}{dt} \][/tex]
[tex]\[ v_z = -6 \phi \sin(2 \mu) \cdot \frac{d\mu}{dt} \][/tex]
Simplifying the expressions, the velocity components become:
[tex]\[ v_x = -12 \alpha \cos^2(\mu) \sin(\mu) \][/tex]
[tex]\[ v_y = 12 \alpha \sin^2(\mu) \cos(\mu) \][/tex]
[tex]\[ v_z = -6 \phi \sin(2 \mu) \][/tex]
2. Acceleration Components
- The acceleration vector [tex]\(\mathbf{a}\)[/tex] is the time derivative of the velocity vector:
[tex]\[ a_x = \frac{dv_x}{dt} = \frac{d}{dt}[-12 \alpha \cos^2(\mu) \sin(\mu)] \][/tex]
Expanding using the product rule:
[tex]\[ a_x = -12 \alpha \left[\cos^2(\mu) \cdot \frac{d}{dt}[\sin(\mu)] + \sin(\mu) \cdot \frac{d}{dt}[\cos^2(\mu)]\right] \][/tex]
Simplifying:
[tex]\[ a_x = -12 \alpha \left[ \cos^2(\mu) (\cos(\mu) \cdot \frac{d\mu}{dt}) + \sin(\mu) \cdot 2 \cos(\mu) \cdot (-\sin(\mu)) \cdot \frac{d\mu}{dt} \right] \][/tex]
[tex]\[ a_x = -12 \alpha \cos(\mu) \cdot \frac{d\mu}{dt} \left[ \cos^2(\mu) - 2 \sin^2(\mu) \right] \][/tex]
Removing the dependency on [tex]\( \frac{d\mu}{dt} \)[/tex]:
[tex]\[ a_x = -12 \alpha [\cos^2(\mu) - 2 \sin^2(\mu)] \cos(\mu) \][/tex]
[tex]\[ a_y = \frac{dv_y}{dt} = \frac{d}{dt}[12 \alpha \sin^2(\mu) \cos(\mu)] \][/tex]
Expanding using the product rule:
[tex]\[ a_y = 12 \alpha \left[\sin^2(\mu) \cdot \frac{d}{dt}[\cos(\mu)] + \cos(\mu) \cdot \frac{d}{dt}[\sin^2(\mu)]\right] \][/tex]
Simplifying:
[tex]\[ a_y = 12 \alpha \left[ \sin^2(\mu) (-\sin(\mu) \cdot \frac{d\mu}{dt}) + \cos(\mu) \cdot 2 \sin(\mu) \cos(\mu) \cdot \frac{d\mu}{dt} \right] \][/tex]
[tex]\[ a_y = 12 \alpha \sin(\mu) \cdot \frac{d\mu}{dt} \left[ 2 \cos^2(\mu) - \sin^2(\mu) \right] \][/tex]
[tex]\[ a_y = 12 \alpha [2 \cos^2(\mu) - \sin^2(\mu)] \sin(\mu) \][/tex]
[tex]\[ a_z = \frac{dv_z}{dt} = \frac{d}{dt}[-6 \phi \sin(2 \mu)] \][/tex]
[tex]\[ a_z = -6 \phi \cdot 2 \cos(2 \mu) \cdot \frac{d\mu}{dt} \][/tex]
Simplifying:
[tex]\[ a_z = -12 \phi \cos(2 \mu) \][/tex]
### Part (b): Evaluating the Dot Product [tex]\( \mathbf{r} \cdot \mathbf{v} \)[/tex]
The dot product is given by:
[tex]\[ \mathbf{r} \cdot \mathbf{v} = x v_x + y v_y + z v_z \][/tex]
Substitute the given expressions:
[tex]\[ x = 4 \alpha \cos^3(\mu), \quad y = 4 \alpha \sin^3(\mu), \quad z = 3 \phi \cos(2 \mu) \][/tex]
[tex]\[ v_x = -12 \alpha \cos^2(\mu) \sin(\mu), \quad v_y = 12 \alpha \sin^2(\mu) \cos(\mu), \quad v_z = -6 \phi \sin(2 \mu) \][/tex]
Calculate the individual products:
[tex]\[ x v_x = (4 \alpha \cos^3(\mu)) (-12 \alpha \cos^2(\mu) \sin(\mu)) \][/tex]
[tex]\[ x v_x = -48 \alpha^2 \cos^5(\mu) \sin(\mu) \][/tex]
[tex]\[ y v_y = (4 \alpha \sin^3(\mu)) (12 \alpha \sin^2(\mu) \cos(\mu)) \][/tex]
[tex]\[ y v_y = 48 \alpha^2 \sin^5(\mu) \cos(\mu) \][/tex]
[tex]\[ z v_z = (3 \phi \cos(2 \mu)) (-6 \phi \sin(2 \mu)) \][/tex]
[tex]\[ z v_z = -18 \phi^2 \cos(2 \mu) \sin(2 \mu) \][/tex]
Using trigonometric identities:
[tex]\[ \cos(2 \mu) \sin(2 \mu) = \frac{1}{2} \sin(4 \mu) \][/tex]
[tex]\[ z v_z = -18 \phi^2 \cdot \frac{1}{2} \sin(4 \mu) \][/tex]
[tex]\[ z v_z = -9 \phi^2 \sin(4 \mu) \][/tex]
Thus, the dot product [tex]\( \mathbf{r} \cdot \mathbf{v} \)[/tex] becomes:enzen
[tex]\[ \mathbf{r} \cdot \mathbf{v} = -48 \alpha^2 \cos^5(\mu) \sin(\mu) + 48 \alpha^2 \sin^5(\mu) \cos(\mu) - 9 \phi^2 \sin(4 \mu) \][/tex]
Therefore, the velocity, acceleration, and the dot product vector for the particle are as derived above.
- Parametric equations for the particle:
[tex]\[ x = 4 \alpha \cos^3(\mu), \quad y = 4 \alpha \sin^3(\mu), \quad z = 3 \phi \cos(2 \mu) \][/tex]
### Part (a): Finding the Velocity and Acceleration
1. Velocity Components
- The velocity vector [tex]\(\mathbf{v}\)[/tex] is obtained by differentiating the position vector with respect to time [tex]\(t\)[/tex]:
[tex]\[ v_x = \frac{dx}{dt} = \frac{d}{dt}[4 \alpha \cos^3(\mu)] \][/tex]
[tex]\[ v_x = 4 \alpha \cdot 3 \cos^2(\mu) \cdot (-\sin(\mu)) \cdot \frac{d\mu}{dt} \][/tex]
[tex]\[ v_x = -12 \alpha \cos^2(\mu) \sin(\mu) \cdot \frac{d\mu}{dt} \][/tex]
[tex]\[ v_y = \frac{dy}{dt} = \frac{d}{dt}[4 \alpha \sin^3(\mu)] \][/tex]
[tex]\[ v_y = 4 \alpha \cdot 3 \sin^2(\mu) \cdot \cos(\mu) \cdot \frac{d\mu}{dt} \][/tex]
[tex]\[ v_y = 12 \alpha \sin^2(\mu) \cos(\mu) \cdot \frac{d\mu}{dt} \][/tex]
[tex]\[ v_z = \frac{dz}{dt} = \frac{d}{dt}[3 \phi \cos(2 \mu)] \][/tex]
[tex]\[ v_z = 3 \phi \cdot (-2 \sin(2 \mu)) \cdot \frac{d\mu}{dt} \][/tex]
[tex]\[ v_z = -6 \phi \sin(2 \mu) \cdot \frac{d\mu}{dt} \][/tex]
Simplifying the expressions, the velocity components become:
[tex]\[ v_x = -12 \alpha \cos^2(\mu) \sin(\mu) \][/tex]
[tex]\[ v_y = 12 \alpha \sin^2(\mu) \cos(\mu) \][/tex]
[tex]\[ v_z = -6 \phi \sin(2 \mu) \][/tex]
2. Acceleration Components
- The acceleration vector [tex]\(\mathbf{a}\)[/tex] is the time derivative of the velocity vector:
[tex]\[ a_x = \frac{dv_x}{dt} = \frac{d}{dt}[-12 \alpha \cos^2(\mu) \sin(\mu)] \][/tex]
Expanding using the product rule:
[tex]\[ a_x = -12 \alpha \left[\cos^2(\mu) \cdot \frac{d}{dt}[\sin(\mu)] + \sin(\mu) \cdot \frac{d}{dt}[\cos^2(\mu)]\right] \][/tex]
Simplifying:
[tex]\[ a_x = -12 \alpha \left[ \cos^2(\mu) (\cos(\mu) \cdot \frac{d\mu}{dt}) + \sin(\mu) \cdot 2 \cos(\mu) \cdot (-\sin(\mu)) \cdot \frac{d\mu}{dt} \right] \][/tex]
[tex]\[ a_x = -12 \alpha \cos(\mu) \cdot \frac{d\mu}{dt} \left[ \cos^2(\mu) - 2 \sin^2(\mu) \right] \][/tex]
Removing the dependency on [tex]\( \frac{d\mu}{dt} \)[/tex]:
[tex]\[ a_x = -12 \alpha [\cos^2(\mu) - 2 \sin^2(\mu)] \cos(\mu) \][/tex]
[tex]\[ a_y = \frac{dv_y}{dt} = \frac{d}{dt}[12 \alpha \sin^2(\mu) \cos(\mu)] \][/tex]
Expanding using the product rule:
[tex]\[ a_y = 12 \alpha \left[\sin^2(\mu) \cdot \frac{d}{dt}[\cos(\mu)] + \cos(\mu) \cdot \frac{d}{dt}[\sin^2(\mu)]\right] \][/tex]
Simplifying:
[tex]\[ a_y = 12 \alpha \left[ \sin^2(\mu) (-\sin(\mu) \cdot \frac{d\mu}{dt}) + \cos(\mu) \cdot 2 \sin(\mu) \cos(\mu) \cdot \frac{d\mu}{dt} \right] \][/tex]
[tex]\[ a_y = 12 \alpha \sin(\mu) \cdot \frac{d\mu}{dt} \left[ 2 \cos^2(\mu) - \sin^2(\mu) \right] \][/tex]
[tex]\[ a_y = 12 \alpha [2 \cos^2(\mu) - \sin^2(\mu)] \sin(\mu) \][/tex]
[tex]\[ a_z = \frac{dv_z}{dt} = \frac{d}{dt}[-6 \phi \sin(2 \mu)] \][/tex]
[tex]\[ a_z = -6 \phi \cdot 2 \cos(2 \mu) \cdot \frac{d\mu}{dt} \][/tex]
Simplifying:
[tex]\[ a_z = -12 \phi \cos(2 \mu) \][/tex]
### Part (b): Evaluating the Dot Product [tex]\( \mathbf{r} \cdot \mathbf{v} \)[/tex]
The dot product is given by:
[tex]\[ \mathbf{r} \cdot \mathbf{v} = x v_x + y v_y + z v_z \][/tex]
Substitute the given expressions:
[tex]\[ x = 4 \alpha \cos^3(\mu), \quad y = 4 \alpha \sin^3(\mu), \quad z = 3 \phi \cos(2 \mu) \][/tex]
[tex]\[ v_x = -12 \alpha \cos^2(\mu) \sin(\mu), \quad v_y = 12 \alpha \sin^2(\mu) \cos(\mu), \quad v_z = -6 \phi \sin(2 \mu) \][/tex]
Calculate the individual products:
[tex]\[ x v_x = (4 \alpha \cos^3(\mu)) (-12 \alpha \cos^2(\mu) \sin(\mu)) \][/tex]
[tex]\[ x v_x = -48 \alpha^2 \cos^5(\mu) \sin(\mu) \][/tex]
[tex]\[ y v_y = (4 \alpha \sin^3(\mu)) (12 \alpha \sin^2(\mu) \cos(\mu)) \][/tex]
[tex]\[ y v_y = 48 \alpha^2 \sin^5(\mu) \cos(\mu) \][/tex]
[tex]\[ z v_z = (3 \phi \cos(2 \mu)) (-6 \phi \sin(2 \mu)) \][/tex]
[tex]\[ z v_z = -18 \phi^2 \cos(2 \mu) \sin(2 \mu) \][/tex]
Using trigonometric identities:
[tex]\[ \cos(2 \mu) \sin(2 \mu) = \frac{1}{2} \sin(4 \mu) \][/tex]
[tex]\[ z v_z = -18 \phi^2 \cdot \frac{1}{2} \sin(4 \mu) \][/tex]
[tex]\[ z v_z = -9 \phi^2 \sin(4 \mu) \][/tex]
Thus, the dot product [tex]\( \mathbf{r} \cdot \mathbf{v} \)[/tex] becomes:enzen
[tex]\[ \mathbf{r} \cdot \mathbf{v} = -48 \alpha^2 \cos^5(\mu) \sin(\mu) + 48 \alpha^2 \sin^5(\mu) \cos(\mu) - 9 \phi^2 \sin(4 \mu) \][/tex]
Therefore, the velocity, acceleration, and the dot product vector for the particle are as derived above.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.